2004
DOI: 10.1158/1078-0432.ccr-0661-03
|View full text |Cite
|
Sign up to set email alerts
|

Src Kinase and Mitogen-Activated Protein Kinases in the Progression from Normal to Malignant Endometrium

Abstract: Purpose: The purpose of this research was to determine whether a correlation exists between the levels of activated mitogen-activated protein kinase (MAPK) and Src kinases and the progression from normal to malignant endometrium.Experimental Design: We measured total and phosphorylated levels for extracellular signal-regulated kinase 1/2, p38, stress-activated protein kinase/c-Jun NH 2 -terminal kinase, and Src kinases from 33 frozen endometrial adenocarcinomas and 38 benign endometrial specimens by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
2
11
0
4
Order By: Relevance
“…Consistent with our results, active, phospho-JNK levels coincided with a decrease in estrogen and progesterone levels, which induced apoptosis in cultured endometrial cells [42,43]. Endometrial adenocarcinomas exhibited increased JNK expression relative to benign endometrium but no significant increase in JNK phosphorylation/activation was detected in tumors of increasing grade [12], suggesting that JNK does not exhibit oncogenic activity associated with progression to malignancy. However, JNK may also function as a tumor suppressor, regulating apoptosis and response to chemotherapy [7,8,11] and, prior to this study, the role of JNK in apoptotic responses in endometrial cancer cells had not been addressed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our results, active, phospho-JNK levels coincided with a decrease in estrogen and progesterone levels, which induced apoptosis in cultured endometrial cells [42,43]. Endometrial adenocarcinomas exhibited increased JNK expression relative to benign endometrium but no significant increase in JNK phosphorylation/activation was detected in tumors of increasing grade [12], suggesting that JNK does not exhibit oncogenic activity associated with progression to malignancy. However, JNK may also function as a tumor suppressor, regulating apoptosis and response to chemotherapy [7,8,11] and, prior to this study, the role of JNK in apoptotic responses in endometrial cancer cells had not been addressed.…”
Section: Discussionsupporting
confidence: 89%
“…However, since our data show that JNK can be activated independently of PKCd and higher-grade tumors retain JNK expression and activity [12], JNK activation, by PKCd-independent pathways, may mediate apoptotic responses to DNA damage in endometrial adenocarcinoma, despite a reduction in PKCd expression.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…3a). Elevated levels of phosphorylated JNK have been found in breast tumors [41]. JNK activation has been shown to mediate the invasive activity of breast cancer cells [42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from this laboratory demonstrated that active kinases are elevated in benign when compared to cancerous endometrium raising the possibility that elevation of active kinases in benign endometrium could contribute to the endometrial oncogenic transformation [10]. Additional work demonstrated that c-Src promoted tamoxifen agonist activity in Ishikawa endometrial cells [11].…”
Section: Introductionmentioning
confidence: 92%